Maximizing the Petroclival Region Exposure Via a Suboccipital Retrosigmoid Approach: Where Is the Intrapetrous Internal Carotid Artery?. Issue 2 (31st March 2015) - Colasanti, Roberto; Tailor, Al-Rahim A; Lamki, Tariq; Zhang, Jun; Ammirati, Mario
Abstract: BACKGROUND: Recent reports have validated the use of retrosigmoid approach extensions to deal with petroclival lesions. OBJECTIVE: To describe the topographic retrosigmoid anatomy of the intrapetrous internal carotid artery (IICA), providing guidelines for maximizing the petroclival region exposure via this route. METHODS: The IICA was exposed bilaterally in 6 specimens via a retrosigmoid approach in the semisitting position. Its topographic relationship with pertinent posterolateral cranial base landmarks was quantified with neuronavigation. RESULTS: Safe exposure of the IICA and the surrounding inframeatal/petroclival regions was accomplished in all specimens. On average, the IICA genu was 15.08 mm anterolateral to the XI nerve in the jugular foramen, 16.18 mm anteroinferolateral to the endolymphatic sac, and 10.63 mm anteroinferolateral to the internal acoustic meatus. On average, the IICA horizontal segment was 9.92 mm inferolateral to the Meckel cave, and its midpoint was 19.96 mm anterolateral to the XI nerve in the jugular foramen. The mean distance from the IICA genu to the cochlea was 1.96 mm. The genu and the midpoint of the horizontal segment of the IICA were exposed at a depth of approximately 14.50 mm from the posterior pyramidal wall with the use of different drilling angles (49.74° vs 39.54°, respectively). CONCLUSION: Knowledge of the IICA general relationship with these landmarks (combined with a careful assessment of the preoperative imaging and with the use of intraoperative navigation and micro-Doppler) may help to enhance the inframeatal/petroclival region exposure via a retrosigmoid route, maximizing safe inframeatal and suprameatal petrous bone removal while minimizing neurovascular complications.